A Descriptive Study for the Impacts of Using Social Media on the Studies of University Students in Pakistan (A Literature Review.) - Mustafa, Sadaf (European Scientific Journal, ESJ, 2018)
This research paper deals with the influence and contribution of Social Media for the studies of students in universities of Pakistan. Detail review of literature is adopted as methodology of this paper. The main objective of this study is to highlight the pros and cons of using social media by the students and emphasize on the positive usages. Mixed results are found while analyses were made on the basis of literature reviewed. It is observed that the use of social media and specifically social networking websites does not always have negative impacts. There are also some positive insights those are detailed in the paper under study. If correctly analyzed and appropriate strategies are formulated and implemented for the use of social media; it will certainly bring improvements in the knowledge and study patterns of university students. It is observed that social networks are also being used by the research students. Therefore, this paper will also help support in the field of research.